MAGGnet: An international network to foster mitigation of agricultural greenhouse gases. Issue 3 (3rd July 2016) - Liebig, M.A.; Franzluebbers, A.J.; Alvarez, C.; Chiesa, T.D.; Lewczuk, N.; Piñeiro, G.; Posse, G.; Yahdjian, L.; Grace, P.; Cabral, O. Machado Rodrigues; Martin-Neto, L.; de Aragão Ribeiro Rodrigues, R.; et al.
ABSTRACT: Research networks provide a framework for review, synthesis and systematic testing of theories by multiple scientists across international borders critical for addressing global-scale issues. In 2012, a GHG research network referred to as MAGGnet (Managing Agricultural Greenhouse Gases Network) was established within the Croplands Research Group of the Global Research Alliance on Agricultural Greenhouse Gases (GRA). With involvement from 46 alliance member countries, MAGGnet seeks to provide a platform for the inventory and analysis of agricultural GHG mitigation research throughout the world. To date, metadata from 315 experimental studies in 20 countries have been compiled using a standardized spreadsheet. Most studies were completed (74%) and conducted within a 1–3-year duration (68%). Soil carbon and nitrous oxide emissions were measured in over 80% of the studies. Among plant variables, grain yield was assessed across studies most frequently (56%), followed by stover (35%) and root (9%) biomass. MAGGnet has contributed to modeling efforts and has spurred other research groups in the GRA to collect experimental site metadata using an adapted spreadsheet. With continued growth and investment, MAGGnet will leverage limited-resource investments by any one country to produce an inclusive, globally shared meta-database focused on the science of GHG mitigation.